Estimation and Analysis of Solar Radiation on Horizontal and Inclined Surface for Baghdad City - Ahmed, Basheer Khaleel; Younis , Ghada Ghanim; Abdalwahid, Zakria (Iraqi Journal of Science, 2021)
The knowledge of the quantity of total solar radiation on horizontal and inclined surfaces is very important in the calculations of heating and cooling loads in architecture and in the design of certain solar energy applications such as photovoltaic and solar collectors. This paper estimates the total solar radiation on inclined surfaces in Baghdad (Lat. 330 21' N 440 14' long and 34m above MSL). A good model was used to estimate hourly total solar radiation on the inclined surface with different elevations (150, 300, 450, 600, 750, 900) from a horizontal surface. The mean hourly, daily and monthly variation of total solar radiation on horizontal and inclined surfaces were drawn and discussed. The optimum tilt angle over a period of a year was drawn and discussed. Linear regression equations correlating the mean hourly solar radiation on an inclined surface with mean hourly solar radiation on a horizontal surface was deduced with high correlation coefficient (0.98 – 0.99).